Skills and strategies for coaching soccer - Hargreaves, Alan 1933- (Human Kinetics, 2010)
Relevant for soccer coaches of beginner, intermediate, as well as, advanced players. Fully updated and revised topics include passing, ball control, shooting, tackling, heading, tactics and systems of play for both defense and offense. Philosophy and team management advice accompanies coaching instruction on skills and tactics. Skills are covered in a progressive manner to get optimum results from players in match situations. Drills divided by skill level - beginner, intermediate, advanced - accompanied by informative, illustrated diagrams and photos. Includes All Star drills for advanced players.